(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
The microbiological quality and safety of raw milk from 60 dairy farms in Madurai were determined. Milk samples were collected at 60 centers from four regions, namely northern, eastern, western and southern (NEWS) according to stratified random sampling design. Samples were analyzed for Total plate count (TPC), psychrotrophs, thermophiles, Staphylococcus aureus, coliform, Escherichia coli 0157: H7 and Salmonella. The mean counts per ml for TPC, psychrotrophs and thermophiles were 12.5x106, 5x103 and 6.85x103 respectively. From the 60 milk samples tested, coliform bacteria contaminated approximately 90% and 70% were E. coli positive, with mean counts ranged from 103 to 104 cfu ml-1. S. aureus was isolated from more than 61.7% of the samples and the mean count per ml was 6.2x103. Meanwhile, E. coli 0157: H7 was also detected in 39 (65%) samples. However, Salmonella was only detected in 8 (13.3%) of the samples with the southern region having the highest frequency of isolation. Bangladesh J. Sci. Ind. Res. 48(2), 109-114, 2013 DOI: http://dx.doi.org/10.3329/bjsir.v48i2.15741